Why borrow from Peter when Paul can afford it? Reverse homodigital artery flap for fingertip reconstruction - Narayanamurthy Sundaramurthy; Surya Rao Rao Venkata Mahipathy; Alagar Raja Durairaj (Indian Journal of Plastic Surgery)
Background: Fingertip injuries that are complicated by pulp loss, bone or tendon exposure will need a flap cover. Cross finger flap is commonly used to cover such defects. However, patients are apprehensive about injuring the uninjured finger as a donor site. Reverse homodigital artery flap (RHAF) can provide reliable vascularised cover to such defects. Aims: This study aims to assess the functional and aesthetic outcomes along with the patient satisfaction of RHAFs done for fingertip defects. Materials and Methods: RHAFs done in 18 patients operated between August 2015 and October 2016 were retrospectively analysed on flap survival, sensory recovery, range of movements, hypersensitivity, cold intolerance, flexion contracture and donor site morbidity. Results: Seventeen of the 18 flaps done survived completely. One flap had partial necrosis of 3 mm that healed conservatively. Middle finger of the right hand was the most commonly injured finger. Touch, pain and pressure sensations recovered in 8–12 weeks. Two-point discrimination was 4.5 mm at 6 months. The deficit of 5° s was present at distal interphalangeal joint during active flexion at 6 months. Cold intolerance and flexion contracture were not seen and 2 instances of hypersensitivity at 2 months got cured conservatively after 4 months. Overall satisfaction of patients was 8/10. Conclusion: RHAF provides single staged well-vascularised cover for fingertip injuries with good sensory recovery without damaging the adjacent uninjured finger. Hence, it can be a reliable flap for fingertip reconstruction in selected cases.